Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What is $\sum\limits_{n=0}^\infty \frac1{(3n+1)^2}$?

share|improve this question
4  
The sum is easily expressed in terms of the Lerch transcendent: $\dfrac19 \Phi\left(1,2,\dfrac13\right)$. There is an alternative expression in terms of the trigamma function: $\dfrac19\psi^{(1)}\left(\dfrac13\right)$, but deriving that form is a bit more complicated to do... –  J. M. Feb 8 '12 at 17:18
4  
The title and the question are asking two different things: the question asks for squares of (numbers that are of the form $3n+1$), whereas I at least parsed the title as asking for (squares of numbers) that are of the form $3n+1$; the sum in (my interpretation of) the title has an explicit elementary form, as opposed to the sum of the question... –  Steven Stadnicki Feb 8 '12 at 17:54
1  
See mathoverflow.net/questions/87348/… by, one assumes, the same person. –  Will Jagy Feb 8 '12 at 21:03
add comment

5 Answers 5

To expand on my comment, two functions here are relevant: the Lerch transcendent

$$\Phi(z,s,a)=\sum_{k=0}^\infty \frac{z^k}{(k+a)^s}$$

and the polygamma function

$$\psi^{(k)}(z)=\frac{\mathrm d^{k+1}}{\mathrm dz^{k+1}}\log\Gamma(z)=(-1)^{k+1}k!\sum_{j=0}^\infty \frac1{(z+j)^{k+1}}$$

where the series expression can be easily derived from differentiating the gamma function relation $\Gamma(z+1)=z\Gamma(z)$ an appropriate number of times

$$\psi^{(k)}(z+1)=\psi^{(k)}(z)+\frac{(-1)^k k!}{z^{k+1}}$$

and recursing as needed.

Comparing these definitions with the series at hand, we find that

$$\Phi\left(1,2,\frac13\right)=\sum_{k=0}^\infty \frac1{(k+1/3)^2}$$

which almost resembles the OP's series, save for a multiplicative factor:

$$\frac19\Phi\left(1,2,\frac13\right)=\sum_{k=0}^\infty \frac1{9(k+1/3)^2}=\sum_{k=0}^\infty \frac1{(3k+1)^2}$$

For the polygamma route, we specialize here to the trigamma case:

$$\psi^{(1)}(z)=\sum_{j=0}^\infty \frac1{(z+j)^2}$$

Letting $z=\frac13$, we have

$$\psi^{(1)}\left(\frac13\right)=\sum_{j=0}^\infty \frac1{(j+1/3)^2}$$

and we again see something familiar. Thus,

$$\sum_{k=0}^\infty \frac1{(3k+1)^2}=\frac19\Phi\left(1,2,\frac13\right)=\frac19\psi^{(1)}\left(\frac13\right)$$

share|improve this answer
add comment

According to Maple solution is given by :

$$\displaystyle\sum_{n=0}^{\infty} \frac{1}{(3n+1)^2} = \frac{1}{9} \Psi\left(1,\frac{1}{3}\right)$$

where $\Psi\left(1,\frac{1}{3}\right)$ is polygamma function .

share|improve this answer
add comment

Some numbers are negative, so the title (not the actual statement, though) may refer to this one, easier to do: $$ \sum_{k=-\infty}^\infty \frac{1}{(3k+1)^2} = \frac{4\pi^2}{27} $$

share|improve this answer
add comment

The sum is $$\frac19{\Psi(1,\frac13)}$$

where $\Psi$ is the Poligamma function

share|improve this answer
add comment

The sum can express $$\begin{align} & \sum\limits_{n=0}^{\infty }{\frac{1}{{{(3n+1)}^{2}}}} \\ & =\frac{1}{9}\left[ \frac{{{\Gamma }''}(1/3)}{\Gamma (1/3)}-{{\left( \frac{{\Gamma }'(1/3)}{\Gamma (1/3)} \right)}^{2}} \right] \\ & =1+\frac{1}{9}\int_{0}^{\infty }{\frac{t{{\mathrm{e}}^{-t/3}}}{{{\mathrm{e}}^{t}}-1}\mathrm{d}t} \\ \end{align}$$ But it can't find the specific value.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.